EC50 of Epidural Ropivacaine Combined With Dexmedetomidine for Labor Analgesia. Issue 10 (October 2018) - Zhang, Wp; Li, Cuiling
Abstract : Background: It has been reported that the optimal concentration of epidural dexmedetomidine for labor analgesia is 0.5 μg/mL when combined with 0.1% ropivacaine. This study investigated the median effective concentration (EC50 ) of epidural ropivacaine for labor analgesia when combined with 0.5 μg/mL dexmedetomidine. Materials and Methods: Sixty full-term primiparas were enrolled and divided into 2 groups in this prospective study. Group D received 10 mL solution (ropivacaine+0.5 μg/mL dexmedetomidine) in the induction of epidural anesthesia, and group C (control group) received 10 mL of ropivacaine alone. The dose of epidural ropivacaine was decided by using the up-and-down sequential allocation method with an initial concentration of 0.1%×0.01% gradient. Effective analgesia was defined as the visual analogue scale for pain as ⩽3 within 30 minutes after epidural injection when cervical dilation is about 2 cm. The EC50 of ropivacaine was calculated by the Massey formula. Hemodynamic parameters, the stages of labor, and fetal heart rate were recorded. Neonatal Apgar scores and umbilical artery pH were also recorded. The side effects, if any, were noted. Results: The EC50 of ropivacaine was 0.062% (95% confidence interval [CI], 0.058%-0.066%) in the group D, and 0.083% (95% CI, 0.077%-0.089%) in the group C, there was a significant difference between the groups ( P <0.05). Conclusions: The EC50 of epidural ropivacaine for labor analgesia was 0.083% (95% CI, 0.077%-0.089%) and decreased to 0.062% (95% CI, 0.058%-0.066%) when combined with 0.5 μg/mL dexmedetomidine (http://www.chictr.org.cn, registration number: ChiCTR-OPC-16008548).